2012
DOI: 10.1158/1078-0432.ccr-12-0110
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Studies of Sirolimus Alone or in Combination with Pharmacokinetic Modulators in Advanced Cancer Patients

Abstract: Purpose Sirolimus is the eponymous inhibitor of the mammalian target of rapamycin (mTOR); however, only its analogues have been approved as cancer therapies. Nevertheless, sirolimus is readily available, has been well-studied in organ transplant patients, and demonstrates efficacy in several preclinical cancer models. Experimental Design Three simultaneously conducted phase I studies in advanced cancer patients utilized an adaptive escalation design to find the dose of oral, weekly sirolimus alone or in comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…At the MTD of 100 mg/m 2 , the C max of nab -rapamycin was 3227.61 ng/mL, which is significantly higher than C max of rapamycin levels achieved in other studies: the C max of 15.5 ng/mL reported with 5 mg oral rapamycin (45), C max of 37.9 ng/mL reported with 9 mg oral rapamycin (46), C max of 57.72 ng/mL reported with 60 mg oral rapamycin (47), and day 5 rapamycin C max of 133.9 ng/mL after 5 days of IV daily administration of temsirolimus at 19.1 mg/m 2 (48). As expected, the half-life of rapamycin from nab -rapamycin was relatively long at 40–91 hours across the tested dose range and was 63 hours at the MTD of 100 mg/m 2 , similar to the half-life of 61–69 hours for oral rapamycin and IV temsirolimus and 45–52 hour for deferolimus given by weekly IV infusion (35, 36, 49, 50).…”
Section: Discussionmentioning
confidence: 55%
“…At the MTD of 100 mg/m 2 , the C max of nab -rapamycin was 3227.61 ng/mL, which is significantly higher than C max of rapamycin levels achieved in other studies: the C max of 15.5 ng/mL reported with 5 mg oral rapamycin (45), C max of 37.9 ng/mL reported with 9 mg oral rapamycin (46), C max of 57.72 ng/mL reported with 60 mg oral rapamycin (47), and day 5 rapamycin C max of 133.9 ng/mL after 5 days of IV daily administration of temsirolimus at 19.1 mg/m 2 (48). As expected, the half-life of rapamycin from nab -rapamycin was relatively long at 40–91 hours across the tested dose range and was 63 hours at the MTD of 100 mg/m 2 , similar to the half-life of 61–69 hours for oral rapamycin and IV temsirolimus and 45–52 hour for deferolimus given by weekly IV infusion (35, 36, 49, 50).…”
Section: Discussionmentioning
confidence: 55%
“…We did not demonstrate a significant reduction in phospho‐p70S6K in circulating PBMCs at 2 hours after temsirolimus or predose on day 36 of cycles 1 to 3, although as noted above, temsirolimus‐related toxicity meant that the majority of patients were dosed inconsistently with consequent reduction in drug exposure. Reduction in p70S6K phosphorylation in PBMCs is seen with single‐agent sirolimus at 48 hours after dose and in PBMCs and tumor biopsies after temsirolimus therapy . However, p70S6K was not consistently reduced in the temsirolimus single‐agent pediatric study, in which only two dose levels (25 and 150 mg/m 2 ) showed a reduction at 8 hours after dose but not at other time points (1, 2, 24, and 168 hours after dose) .…”
Section: Discussionmentioning
confidence: 93%
“…Reduction in p70S6K phosphorylation in PBMCs is seen with single-agent sirolimus at 48 hours after dose and in PBMCs and tumor biopsies after temsirolimus therapy. 31,32 However, p70S6K was not consistently reduced in the temsirolimus single-agent pediatric study, in which only two dose levels (25 and 150 mg/m 2 ) showed a reduction at 8 hours after dose but not at other time points (1, 2, 24, and 168 hours after dose). 5 The preceding pediatric vinblastine/sirolimus phase I study also did not show significant reduction of p70S6K at 28 days after dose.…”
Section: Discussionmentioning
confidence: 93%
“…Sirolimus is an immunosuppressive agent that blocks the molecular target of rapamycin (mTOR inhibitor) [2]. This blockade leads to the inhibition of T-and B-cell proliferation and immunoglobulin production.…”
Section: Letter To the Editor Edibe Minarecimentioning
confidence: 99%